Current and future challenges of preventing outbreaks of highly pathogenic avian influenza - Davis, Heather Ann (Kansas State University, 2016)
Avian influenza (AI) is a zoonotic disease that has garnered much attention in recent years due to its detrimental effects on poultry, producers and potentially human health. This disease can be extremely fatal to domestic poultry, killing as high as 90-100% of the flock. This virus has the potential to cause devastation to and loss of entire flocks. AI is typically spread between wild fowl and domestic poultry with a zoonotic potential to also affect human health as well as other animals. Its spread also has a massive economic impact due to the decreased amounts of available poultry products to consumers around the world. This report will examine the worldwide history and epidemiology of highly pathogenic avian influenza (HPAI). In the last ninety-two years, there have been five recorded outbreaks of HPAI in the United States (US). Globally, notable outbreaks have occurred in Italy (1997-2001), the Dutch region of Europe (2003), Canada (2004), and more recently, in Asia. Preventative measures will be examined in this report. In particular, biosecurity, quarantine, surveillance, and eradication are some of the most widely recognized and accepted ways to help prevent and control HPAI outbreaks. However, none of these methods are failsafe strategies to completely prevent or control the spread of HPAI. This report will focus on an additional preventative measure - currently available and potential future vaccination programs. There is a global shift toward procuring poultry that are AI-free as well as unvaccinated for AI. This is, in part, due to the limitations of currently available vaccines in completely ridding poultry of this disease. Vaccinations may reduce the amount of virus in infected birds, but this does not prevent birds from becoming infected. When addressing the control and eradication of HPAI, some future challenges include viral mutations, intermingling of domesticated and wild birds, and vaccine development. Because of the current limitations of vaccines and future challenges in controlling the spread of infection, there is no one single solution to this problem. It will require a multi-faceted approach.
Keywords: Biosecurity; Surveillance; Quarantine; Eradication; VaccinationHighly Pathogenic Avian Influenza